Cholamandal Artists’ Village: An Interaction Between the Tradition and Modernity (India, the Madras School) - Horbachova, Valeriia (HUDPROM: The Ukrainian Art and Design Journal, 2023)
Based on the analysis of scientific literature, a successful example of an independent and self-organized community of Cholamandal artists was studied as a continuation of the artistic searches and experiments of the Madras school during the second half of the 20th – early 21st centuries. The prerequisites for the emergence and development of the Cholamandal commune headed by K. Paniker are analyzed. The activities of individual artists of the art association – painters (K. Paniker, R. Pooviah, T. Tarani), graphic artists (K. Haridasan, K. Ramanujam), sculptors (C. Patnaik, S. Nandagopal) and others are considered. The plot and thematic features of their achievements are clarified – the search for original interaction with folk, religious and tantric art is characteristic for these artists. The special position of folk art becomes one of the distinguishing features of the association’s activities. Traditions and their inheritance are seen as an important communicative part and as a source of experiments for modern practices, which, in turn, supported the cross-platform nature of Cholamandal. The settlement included not only workshops and an exhibition gallery, but also an open-air theater for dancing and theatrical performances, a textile workshop, a library and all the necessary infrastructure for everyday life. Cholamandal artists are known for their experiments with traditional Indian techniques and materials such as terracotta, bronze casting, a combination of fresco and oil painting. They combined these techniques with contemporary styles and themes to create unique works of art, reflecting the richness and complexity of India’s artistic tradition. The Cholamandal commune also played an important role in popularizing of modern Indian art among a wide audience. Art exhibitions and events held at Cholamandal attracted art enthusiasts and collectors from all over India and abroad and have helped bring Indian contemporary art to the attention of the global art scene.